2010
DOI: 10.5558/tfc86043-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing forest biomass for bioenergy: Operational challenges and cost considerations

Abstract: Sustainability assessments and biomass inventories often neglect the operational challenges involved in the harvesting of forest biomass for bioenergy. Thus, concerns that increasing demands for biomass will lead to greater environmental impacts, particularly on soil productivity, need to be considered from an operations perspective that takes into consideration the technical and cost limitations to biomass recovery. We examine operational forest biomass recovery potential of harvest residue (slash) for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…These three latter factors overlap in defining the opportunities for harvesting residue recovery. For example, Ralevic et al (2010) found that it was technically possible to recover only 25% to 59% of the total available volume of harvesting residues on two sites in northern Ontario. The amount of harvesting residue that can be cost-effectively recovered will also depend on a range of economic factors (e.g., Grushecky et al 2007).…”
Section: Estimating Forest Biomass Supplymentioning
confidence: 99%
“…These three latter factors overlap in defining the opportunities for harvesting residue recovery. For example, Ralevic et al (2010) found that it was technically possible to recover only 25% to 59% of the total available volume of harvesting residues on two sites in northern Ontario. The amount of harvesting residue that can be cost-effectively recovered will also depend on a range of economic factors (e.g., Grushecky et al 2007).…”
Section: Estimating Forest Biomass Supplymentioning
confidence: 99%
“…Ainsi, ces trois facteurs concourent à définir le potentiel de récupération des résidus de coupe. Par exemple, Ralevic et al (2010) ont constaté qu'il était techniquement possible de récupérer seulement 25 % à 59 % du volume total de rési-dus de coupe dans deux sites du nord de l'Ontario. La quantité de résidus de coupe qui peut être récupérée de façon rentable dépend également d'une vaste gamme de facteurs économiques (ex : Grushecky et al 2007).…”
Section: Estimation De La Réserve De Biomasse Forestièreunclassified
“…In a modeling study of the amount of biomass generated by natural disturbances in Canadian forests, Dymond et al (2010) estimated that the MPB outbreak could generate an average of 16.8 M dry tonnes of dead wood per year between 2005 and 2020. It is important to note, however, that biomass availability is often limited by economic factors (Ralevic et al 2010), which suggests that these previous studies may not adequately reflect the actual amounts of biomass that are likely to enter bioenergy feedstock supply chains.…”
Section: Mpb-killed Wood As a Potential Wood Pellet Feedstockmentioning
confidence: 99%
“…The payments were designed to allow operators to develop more cost-effective systems for biomass collection in order for the systems to be self-sustaining by the end of the subsidy period (Sedjo 2010, Stubbs 2011. Such a system, if employed in BC, could make the recovery of MPB-killed biomass economically feasible, although given the scale of the MPB outbreak (Eng et al 2006, Ralevic and Layzell 2006, FPB 2007, MFLNRO 2012a), a two-year subsidy would be woefully ineffective given the precarious position of wood pellet producers. A CAN$50 per tonne The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 34.218.44.141 on 05/11/18…”
Section: Mpb-killed Wood As a Potential Wood Pellet Feedstockmentioning
confidence: 99%
See 1 more Smart Citation